The comparative effects of exercise type on motor function of patients with Parkinson’s disease: A three-arm randomized trial - Li, Fang; Wang, Dongyu; Ba, Xiaohong; Liu, Zhan; Zhang, Meiqi (Frontiers in Human Neuroscience, 2022)
Background: Yang-ge dancing (YG) is a culturally specific exercise in which people are required to perform motor skills in coordination with rhythmic music. As an integrated exercise modality with both physical (decelerating the progression of age-related motor function degeneration) and mental benefits, it has gained great population in China, especially among middle-aged and older adults. It remains largely unknown whether YG effectively improved the main symptoms (like motor function) of Parkinson’s disease (PD), while conventional exercise (CE) rehabilitation program has been recommended in the hospital setting. To this end, this study aimed to investigate the comparative effects of exercise modality on motor function of PD patients. Methods: Fifty-one PD patients were randomly assigned to YG, CE, or CE plus rhythmic music (CEM) group. Participants in each group performed 60 minutes per session, five sessions per week of interventions for 4 weeks. All the participants were assessed using the Unified Parkinson's Disease Rating Scale – motor examination, Berg balance test, timed-up-and-go test, and Purdue pegboard test. Motor performances were examined before and after the intervention. A 2 × 3 (time × group) mixed multivariate analysis of variance (MANOVA) with repeated measures was performed to detect the intervention effects on the outcome measures. Results: All the three groups were benefited from exercise [Wilks’s lambda = 0.687, F(8,86) = 2.219, p = 0.034, partial eta squared = 0.171]. Compared to the CE, the YG and CEM had additional positive effects in mobility with reference to baseline [t(16) = 5.876, p = 0.001, d = 1.895, t(17) = 2.508, p = 0.016, d = 0.486, and t(13) = 4.990, p = 0.001, d = 1.411]. In addition, compared to CE and CEM [t(17) = -0.177, p = 0.860, d = 0.048, and t(13) = 1.603, p = 0.116, d = 0.333], the YG group further enhanced manual dexterity [t(16) = 4.063, p = 0.001, d = 2.297]. Conclusion: Exercise with RAS optimized mobility in PD, while YG dance specifically contributed to improvement in manual dexterity.